A Novel Multimodal Radiomics Model for Predicting Prognosis of Resected Hepatocellular Carcinoma - He, Ying; Hu, Bin; Zhu, Chengzhan; Xu, Wenjian; Ge, Yaqiong; Hao, Xiwei; Dong, Bingzi; Chen, Xin; Dong, Qian; Zhou, Xianjun (Frontiers in Oncology, 2022)
Abstract Objective: To explore a new model to predict the prognosis of liver cancer based on magnetic resonance imaging (MRI) and computed tomography (CT) imaging data. Methods: A retrospective study of 103 patients with histologically proven hepatocellular carcinoma (HCC) was conducted. Patients were randomly divided into training (n = 73) and validation (n = 30) groups. A total of 1217 radiomics features were extracted from regions of interest on CT and MRI images of each patient. Univariate Cox regression, Spearman’s correlation analysis, Pearson’s correlation analysis, and least absolute shrinkage and selection operator Cox analysis were used for feature selection in the training set, multivariate Cox proportional risk models were established to predict disease-free survival (DFS) and overall survival (OS), and the models were validated using validation cohort data. Multimodal radiomics scores, integrating CT and MRI data, were applied, together with clinical risk factors, to construct nomograms for individualized survival assessment, and calibration curves were used to evaluate model consistency. Harrell’s concordance index(C-index) values were calculated to evaluate the prediction performance of the models. Results: The radiomics score established using CT and MR data was an independent predictor of prognosis (DFS and OS) in patients with HCC (P < 0.05). Prediction models illustrated by nomograms for predicting prognosis in liver cancer were established. Integrated CT and MRI and clinical multimodal data had the best predictive performance in the training and validation cohorts for both DFS[ (C-index(95%CI): 0.858(0.811-0.905) and 0.704(0.563-0.845), respectively)] and OS [C-index(95%CI): 0.893(0.846-0.940) and 0.738(0.575-0.901), respectively]. The calibration curve showed that the multimodal radiomics model provides greater clinical benefits. Conclusion: Multimodal (MRI/CT) radiomics models can serve as effective visual tools for predicting prognosis in patients with liver cancer. This approach has great potential to improve treatment decisions when applied for preoperative prediction in patients with HCC.